Ma glèbe est fruste, plane, vouée aux brouillards... - Bermúdez Medina, Lola (Verbum – Analecta Neolatina, 2013)
The paper presents an analysis of the role played by the landscape (above all, the Belgian Campine) in Georges Eekhoud’s oeuvre. Landscape was particularly prominent in his early work, and it was always associated with the national values presiding the emergence of Belgian literature. The defence of rusticity would be increasingly pervaded by sociological values (resistance against the “universal enlistment towards the bourgeois ideal”) as well as homoerotic values, which are at the root of practically the entire work of the Belgian novelist.